Sympathetic Nervous System Mediates Cardiac Remodeling After Myocardial Infarction in a Circadian Disruption Model - Wang, Yuhong; Jiang, Wanli; Chen, Hu; Zhou, Huixin; Liu, Zhihao; Liu, Zihan; Liu, Zhihao; Zhou, Yuyang; Zhou, Xiaoya; Yu, Lilei; Jiang, Hong (Frontiers in Cardiovascular Medicine, 2021)
Background: Circadian rhythms have a considerable impact on the daily physiology of the heart, and their disruption causes pathology. Several studies have revealed that circadian disruption impaired cardiac remodeling after myocardial infarction (MI); however, the underlying brain-heart mechanisms remain unknown. We aim to discuss whether circadian disruption facilitates cardiac remodeling after MI by activating sympathetic nervous system. Methods: Rats were randomly divided into three groups: Sham group (Sham), MI group (MI), and MI+ circadian disruption group (MI+Dis); rats were treated with PRV injections for trans-synaptic retrograde tracing; rats were randomly divided into two groups: MI+ circadian disruption + Empty Vector+ CNO (Empty Vector), and MI+ circadian disruption + hM4D(Gi)+ CNO (hM4D(Gi)). Results: Circadian disruption significantly facilitated cardiac remodeling after MI with lower systolic function, larger left ventricular volume, and aggravated cardiac fibrosis. Cardiac sympathetic remodeling makers and serum norepinephrine levels were also significantly increased by circadian disruption. PRV virus-labeled neurons were identified in the SCG, PVN, and SCN regions. Ganglionic blockade via DREADD technique suppressed the activity of sympathetic nervous system and significantly alleviated the disruption-related cardiac dysfunction. Conclusion: Circadian disruption adversely affected cardiac remodeling after MI possibly by activating sympathetic nervous system, and suppressing sympathetic activity can attenuate this disruption-related cardiac dysfunction.